Artikel Review: Formulasi Sediaan Tetes Mata untuk Mata Kering - Dewi Rahmawati; Tiara Putri Hartanto; Miftahul Maulidiyah; Silvia Nur Diana Putri; Cantika Putri Amanda; Rizma Salsa Salim; Chindy Elsa Ramadhani; Dzakiah Zhirotul Wida; Fitrul Mubarok (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Eye drops are used for dry eyes, red eyes, allergies, infections, and glaucoma. Evaluation of eye drops includes pH, osmolality, and viscosity, which must be adjusted so that the preparation is comfortable for the eyes and does not cause irritation. This review aims to determine the active ingredients that are suitable for use and the efficacy of these active ingredients in eye drops that are made. Literature searches were conducted using online-based literature search instruments, such as Google Scholar. The results and discussions include several physical and chemical evaluations from several journals. Based on the literature study conducted, it can be concluded that various formulation innovations for the treatment of dry eyes, including lipid-based liposomes, omega-3 fatty acids, and natural ingredients such as castor oil, show great potential in mimicking the function of the natural tear film, reducing fluid evaporation, and supporting regeneration and stability of corneal epithelial cells.